Website-Based System Prototype Development for Classify Student Characteristics - Kencana, Lisdi Inu; Rafrastara, Fauzi Adi; Paramita, Cinantya (Universitas Muhammadiyah Semarang Press, 2022)
Student characteristics are important attributes in understanding their academic abilities and ways of thinking. In the teaching and learning process, the right learning strategy is very important to implement. According to the Hippocrates-Galenus Typology, personality types are categorized into four categories, including sanguinis, choleric, melancholics, and phlegmatics. The Classification of student characteristics using experience and intuition methods often gives inaccurate results and takes a long time to understand their behavior and way of thinking. In our research, we developed a prototype cognitive system website to classify student characteristics at SD Wijaya Kusuma 02 Semarang. There are several stages of the proposed method, including, communication, rapid planning, rapid design modeling, prototype construction, and delivery & feedback deployment. The C4.5 algorithm is applied as the modeling of student characteristics classification. The results showed a fairly good accuracy of 90.08%. It can be concluded that the C4.5 algorithm can classify student characteristics well.